Optimal correlation of non-renewable and renewable generating systems for producing hydrogen and methane by power to gas process - Mehrjerdi, Hasan (International journal of hydrogen energy, 2019)
This paper presents an efficient framework for converting renewable energy to gas and reducing Carbon dioxide (CO2) footprint at the same time. The problem is presented in two levels. The first level is a minimization programming that minimizes operational cost and CO2 of generators. The CO2 is forwarded to the second level. In the second level, Carbon Capture and Storage (CCS) is designed to capture CO2. The CO2 is combined with Hydrogen and makes Methane (CH4). The required Hydrogen is obtained from water electrolyzer that is supplied by the solar system. The capacity and size of water electrolyzer, solar system, and CCS is designed by the planning in the second level while this programming maximizes profit from selling Methane. As a result, the first level presents minimization programming (i.e., minimizing cost and CO2) and the second level presents maximization programming (i.e., maximizing profit). The programming is developed taking into account solar uncertainty. The stochastic programming is implemented to cope with uncertainties. The problem is formulated as binary mixed integer linear programming and solved by GAMS software. The proposed power to gas (P2G) procedure efficiently designs proper solar system and deals with intermittency of solar energy, reduces CO2 footprint, maximizes profit, and minimizes operational cost of generators at the same time. •Operational cost and CO2 is minimized for nonrenewable generators.•Considering Carbon tax operates low-cost and low-polluting units.•Optimal size of solar system is designed equal to 190 MW.•Annualized profit of power to gas system is 1.617 Million $ per year.•Carbon capture system captures 1621.5 (kg/day) of CO2.